Pengaruh Variasi Produk Dan Lokasi Pemasaran Terhadap Keputusan Pembelian Pelanggan Coffeeshop 90o Medan - alfeisha, Dhito; Syahreza, Dina Sarah (JEBIM Prima, 2024)
This research aims to determine the influence of product variations and marketing location on purchasing decisions at 900 Medan coffeeshops. The sampling technique used in this research used nonprobability sampling with purposive sampling, so that the total sample obtained was 100 respondents. The data collection techniques used were literature study, interviews and questionnaires. The data analysis technique used is a multiple linear regression model and hypothesis testing, t test, f test and coefficient of determination. The data has previously been tested using validity tests, reliability tests and classical assumptions, data processing using SPSS 26.0 for windows. Based on the test results, it shows that product variations and marketing locations have a positive and significant effect on purchasing decisions. Based on the R Square statistical test in this research, it was 0.645 or 64.5%, this shows that purchasing decision variables can be influenced by product variation variables and marketing location.